Access to Services: Case of Marginal and Landless Livestock Farmers in Tamil Nadu of India - Sakthivel, K. M.; Khandekar, Prakash; Sasidhar, P. V. K.; Narmatha, N. (International Journal of Bio-resource and Stress Management, 2023)
A study was conducted among 200 households of marginal and landless livestock farmers in rural Tamil Nadu of India to determine the extent of their access to various support services and resources like animal health care, credit, education and common property resources (CPRs). Multistage sampling technique was used to select the respondents. Majority of the households (97.50%) contacted Veterinary Assistant Surgeon (VAS) when their animals fell sick, and 36.50% made 3-4 visits to veterinary dispensary. Nearly 87% households called VAS for home visit, and 57% paid INR 100-150 visit-1 for treatment. 56% households received credit in the past 3 years and not yet paid, while the remaining 44% were free from any debt. For majority of households (73.72%), the chief source of credit was money lenders. Though access to educational services has improved, much impact was not noticeable. CPRs are at the edge of extermination. Delivering the service of mobile veterinary clinics, encouraging veterinary graduates to start private veterinary clinics, conducting awareness campaign on common livestock ailments and management of CPRs, establishing community fodder farms, and improvement in formal credit system accessibility are recommended.